Sunk Costs, Market Contestability, and the Size Distribution of Firms - Kessides, Ioannis N.; Tang, Li (2012)
In this paper we offer a new economic explanation for the observed inter-industry differences in the size distribution of firms. Our empirical estimates based on three temporal (1982, 1987, and 1992) cross-sections of the four-digit US manufacturing industries indicate that increased market contestability, as signified by low sunk costs, tends to reduce the dispersion of firm sizes. These findings provide support for one of the key predictions of the theory of contestable markets: that market forces under contestability would tend to render any inefficient organization of the industry unsustainable and, consequently, tighten the distribution of firms around the optimum.